HUBUNGAN PERSEPSI MAHASISWA TENTANG LINGKUNGAN BELAJAR TERHADAP PRESTASI AKADEMIK DI FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - DANA RIZKI ADILLA SITEPU; DESI ISNAYANTI (LP2MTBM MAKARIOZ, 2021)
Academic success can be measured by academic achievement. Academic achievement can be influenced by learningenvironment factors that such an important thing in the level of academic achievement. The learning environment is allconditions and influences from outside oneself on learning activites. The better learning environment, the higher of studentsto learn so that it will have a good impact on academic achievement. This study aims to determine the relationship betweenstudents perceptions about the learning environment on academic achievement at FK UMSU. This research is a descriptiveanalytic study with cross sectional design. The research sample consisted of 190 students of FK UMSU 2016, 2017, and2018 taken by proportional stratified random sampling method.This research was tested by Kruskal-Wallis. Overall the resultwere quite satisfying on students perceptions of environmental education with total grade of 80,53%. The mean value persubscale shows good results on students perceptions of the educational environment. The average academic achievementin the category is very good. Kruskal-Wallis test analysis obtained p value of 0,000which means there is a relationshipbetween the educational environment and academic achievement. Student perceptions of the learning environment have arelationship with academic achievement in FK UMSU students.